Pressure and Argumentation in Public Controversies: A Dialogical Perspective - van Laar, Jan Albert; Krabbe, Erik C. W. (Informal Logic)

(untitled) (Informal Logic, 2019)
When can exerting pressure in a public controversy promote reasonable outcomes, and when is it rather a hindrance? We show how negotiation and persuasion dialogue can be intertwined. Then, we examine in what ways one can in a public controversy exert pressure on others through sanctions or rewards. Finally, we discuss from the viewpoints of persuasion and negotiation whether and, if so, how pressure hinders the achievement of a reasonable outcome.